(untitled) (Palimpsesto, 2025)
The transition to adulthood of people with intellectual disabilities is a process better understood in its complexity using a relational perspective that involves the family, without minimising the voice of the young people themselves in their future planning. This position not only allows us to understand a process of projection into the future subject to collective decisions of the family, but also contributes to understanding that adulthood does not end or exhaust itself with the normative life course pillars. Through a relational perspective, this paper proposes to understand the ideas about adulthood from young people with intellectual disabilities in a family context and from the negotiations carried out on how they project their future interdependently.